The role of humic-type ligands in the bioavailability and stabilization of dissolved iron in the Western Tropical South Pacific Ocean - Dulaquais, Gabriel; Fourrier, Pierre; Guieu, Cécile; Mahieu, Léo; Riso, Ricardo; Salaun, Pascal; Tilliette, Chloé; Whitby, Hannah (Frontiers in Marine Science, 2023)
The high N2 fixation rate observed in the Lau Basin of the western tropical South Pacific Ocean (WTSP) is fueled by iron (Fe) released from shallow hydrothermal systems. Understanding Fe bioavailability is crucial but the controls on the stability and bioavailability of hydrothermal Fe inputs are still poorly understood. Here, we provide new data on the spatial and vertical distribution of the soluble ubiquitous humic-like ligands (LFeHS) and their associated dissolved Fe (DFe) in the WTSP, including in samples near hydrothermal vents. Our data show that LFeHS are heterogenous ligands with binding sites of both strong and intermediate strengths. These ligands are primarily produced in surface waters and partially mineralized in mesopelagic waters. A substantial fraction of DFe was complexed by LFeHS (mean ~30%). The DFe complexed by LFeHS is likely bioavailable to phytoplankton and LFeHS stabilized Fe released by the mineralization of sinking biomass. However, unsaturation of LFeHS by Fe suggest that part of DFe is not available for complexation with LFeHS. Possible reasons are competition between DFe and other metals, such as dissolved copper, or the inability of LFeHS to access colloidal DFe. The study of two volcanic sites indicates that LFeHS were not produced in these hydrothermal systems. At the active site (DFe ~50 nmol L-1), LFeHS can only partially solubilize the hydrothermal DFe released in this area (1~5.5% of the total DFe). We performed controlled laboratory experiments which show that the observed low solubilization yield result from the inability of LFeHS to solubilize aged Fe oxyhydroxides (FeOx - a kinetically mediated process) and to form stable complexes with Fe(II) species. Our study provides new understanding of the role of LFeHS on the bioavailability and stabilization of hydrothermal DFe.